Death in war and peace loss and grief in England - Jalland, Patricia (Oxford University Press, 2012)
The history of death is a vital part of human history, and a study of dying and grief takes us to the heart of any culture. Since the First World War there has been a tendency to privatize death, and to minimize the expression of grief and the rituals of mourning. Jalland explores the nature and scope of this cultural shift.